Kajian Teoritis Peranan Internal Auditor - Jeanne Asteria Wawolangi; Martinus Sony Erstiawan (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2013)
Internal auditor as internal examination which evaluating all the operation of the organization especially about system internal control, also accompanied external auditor to explain more detailed about all the flow and procedure system internal control and give the reason and benefit about implementation of internal control. Internal auditor has to assure that all the evidence about external or internal transaction are real and objective. If internal auditor find inconsistency about the policy of the firm, so internal auditor has to explain and guide to the right things and also follow up all the audit findings to achieve the goal of the firm. Internal auditor gives all the annually report to all the directors to make a best decision.